Impact of fibroblast activation protein on osteosarcoma cell lines in vitro - DING, LIXIANG (D.A. Spandidos, 2014)
Fibroblast activation protein (FAP) or seprase, which belongs to the group type II integral serine proteases, is an integral membrane serine peptidase. Previous studies have demonstrated that FAP has an effect on tumor growth, proliferation and invasion. However, the cellular functional role that FAP plays in osteosarcoma (OS) remains unknown. The aim of the present study was to investigate the activities of FAP in OS cell lines. The gene expression of FAP was knocked down through a hammerhead ribozyme transgene, and the various functions between the knockdown cells and their control cells were tested using a series of functional assays in vitro. The results indicated that knockdown of FAP markedly reduced the ability of cellular growth, matrix adhesion, migration and invasion in MG-63 and HOS cell lines compared with the control cells (P<0.05). In conclusion, FAP influences OS cells and may play a role in OS tumor progression and metastasis.